2007
DOI: 10.1080/17453670710014527
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with acute hip prosthetic joint infections and outcome of treatment with a rifampinbased regimen

Abstract: Background and purpose Acute prosthetic infection is a serious problem. We report factors related to the incidence of acute infection and results of combined joint debridement and prolonged rifampicin-based antibiotic therapy.Patients and methods Between 1998 and 2004, 14 acute infections occurred after 819 primary hip arthroplasties. The association between patient-related and surgical factors and the risk of infection were analyzed. Infections were treated with multiple joint lavage, debridement, 2 weeks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
101
0
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 48 publications
4
101
0
8
Order By: Relevance
“…Indeed, in only 4 of the 7 patients with single or mixed MRSA infection could the prosthesis be successfully retained. Taken together, the statement of Choong et al (2007) that debridement with retention "may be suitable for patients who are not fit for major revision surgery (and) for those who decline further major surgery" is not based on our treatment concepts. Because Choong et al (2007) highlight the influence of our work on their treatment concept, we would like to emphasize the mentioned differences.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, in only 4 of the 7 patients with single or mixed MRSA infection could the prosthesis be successfully retained. Taken together, the statement of Choong et al (2007) that debridement with retention "may be suitable for patients who are not fit for major revision surgery (and) for those who decline further major surgery" is not based on our treatment concepts. Because Choong et al (2007) highlight the influence of our work on their treatment concept, we would like to emphasize the mentioned differences.…”
mentioning
confidence: 99%
“…In their recent publication, Choong et al (2007) reported the outcome of a treatment protocol for total hip arthroplastyassociated infections (THIs), including debridement with retention and prolonged rifampin-based therapy. Since the authors refer to our treatment concepts, we would like to call attention to the fact that their retrospective study (Choong et al 2007) clearly used different criteria to select patients for retention of the implant than were described in our algorithm . Moreover, the duration of antimicrobial treatment reveals fundamental divergences from our approach.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[4,[6][7][8][9][10][11][12][13][14] Once an infection is diagnosed, a number of therapeutic approaches may be adopted. The selection of a particular approach depends on host factors (age, baseline mobility, comorbidities, etc.…”
Section: Risk Factorsmentioning
confidence: 99%